Strategi Pengembangan Pariwisata dengan Berlandaskan Kebudayaan Lokal di Desa Bebetin Kabupaten Buleleng Provinsi Bali - Berata , Nyoman Candra; Rahmawati, Putu Indah; Widiastini , Ni Made Ary (Jurnal Penelitian Mahasiswa Indonesia, 2024)
Study This is study descriptive purposive qualitative​ For analyze development strategies tourist with based culture local in the village Bebetin regency Buleleng province Bali. Discussion study leads to how method develop tourism in the village Bebetin with based culture local. Study This done during four month withn method data retrieval ie observation, interviews, and documentation. Interview on research This done with head village, chairman POKDARWIS village Bebetin and 3 communities. Result of study This show that potency tourism owned by the village Bebetin is very big especially in the field tour nature and tourism the culture, however development tour in a way sustainable Not yet carried out by the government village so that tourist village bebetin Not yet Can consistent in its development.